Influence of APOE locus on poor prognosis of COVID-19. Issue 6 (June 2021) - Rodrigues, Juliana Carla Gomes; Pinto, Pablo; Leitão, Luciana Pereira Colares; Vinagre, Lui Wallacy Morikawa Souza; Monte, Natasha; Fernandes, Marianne Rodrigues; Khayat, André Salim; de Assumpção, Paulo Pimentel; Santos, Ney Pereira Carneiro dos; Santos, Sidney Emanuel Batista dos
Abstract: The COVID-19 pandemic has infected over 25 million of people worldwide, 5% of whom evolved to death and, among of the active cases, more than 60 thousand are classified as critical or severe. Recent studies revealed that ApoE, a protein encoded by APOE gene, may increase the risk of severe COVID-19 cases. ApoE has been involved with prevention of tissue damage and promotion of adaptative immune response in the lungs. This study investigated frequencies distribution of alleles that alter the ApoE expression in lung tissues to trace a profile of these variants and associate them to COVID-19 clinical outcomes. Data about APOE expression levels was obtained from the Genotype-Tissue Expression Project and the allele frequencies of APOE variants was acquired from the populations included in the phase 3 release of the 1000 Genomes Project. A total of 128 variants showed a significant impact on the APOE expression in lung tissues (p < 0.0001). Linkage Disequilibrium analysis revealed that 98 variants were closely grouped into seven distinct haplotype blocks, of which six were composed of variants that significantly decrease APOE gene expression in the lungs. Most of the haplotypes with higher impact on APOE expression showed greater frequencies in Europeans and lower in Africans, which implies that European populations might be more susceptible to SARS-CoV-2 infection. The present study indicates a potential genetic contribution of APOE expression-modifying variants in modulating the prognosis of COVID-19. Abstract : SARS-CoV-2, COVID-19, susceptibility, APOE, lung.